Leucocyte migration inhibition with inner and outer membranes of mitochondria and insoluble hepatocyte surface membranes prepared from rat liver in patients with chronic hepatitis and cirrhosis. - Ohta, G (1976)
Patients with chronic liver disease were tested for delayed hypersensitivity to the outer and the inner membranes of mitochondria (OMM and IMM) and the insoluble hepatocyte-surface membranes (IHSM), prepared from rat livers, by means of leucocyte migration inhibition technique. Positive reaction to OMM was found in 37% of patients with chronic persistent hepatitis and 35% of those with chronic active hepatitis and 43% of those with liver cirrhosis (P less than 0-05). That to IMM was 55%, 43% and 36% (P less than 0-05) and to IHSM was 37%, 47% and 45% respectively (P less than 0-05). IHSM was found to contain liver-specific components and patients with positive response to IHSM did not reveal at all a positive reaction to rat renal cell-surface membranes. The incidence of positive response to IHSM was significantly higher (54-2%) in patients with the present or previous infection with HBAg than in HBAg-non-infected patients (21-4%) (P less than 0-05). And there seemed to be a good correlation between a degree of cellular response to purified HBsAg and that to IHSM in these HBAg-infected patients. No correlation, however, was found between that to purified HBsAg and that to OMM or IMM in the same patients. This suggested that the cellular response to either HBsAg or IHSM, both related closely, may play a role in the perpetuation of chronic liver disease.